Domestic workers and poverty: A comparative approach on Turkish and migrant woman - Avcı, Safiye Gül (My University, 2019)
This thesis aims to understand multi-dimensional poverty of local and foreign female domestic workers. Based on semi-structured in-depth interviews conducted in İstanbul, it aims to discover multiple but interrelated causes of their poverty through a gender-sensitive approach. To this end, domestic workers’ narratives are analysed under three main parts along with the sub-headings: The first part focuses on the impoverishing effects of the patriarchy and the material deprivation on domestic workers’ life choices - education and marriage. In this way, the study aims to understand how material poverty, lack of education and conventional values weaken women and affect their participation into the labour force market. The second part dwells on domestic workers’ experiences while performing their job and the related problems in detail. In this part, especially the effects of domestic service as an informal employment field is analysed to understand how it impoverishes their lives. The third part concentrates on the influences of the job on women’s individual and family life and their future prospects. While giving considerations to whether the job enhances their lives on an individual basis, the study also questions if female domestic workers have a control over their income. Through these analyses, this thesis studies women domestic workers’ poverty multi-dimensionally and does not trap the poverty discussion only into monetary issues, and thus making it possible to understand and explore other impoverishing and weakening factors which comprise an important part of women’s poverty.
Tez (Yüksek Lisans) - Yıldız Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 2019
Keywords: Poverty; Domestic service; Women domestic workers; Yoksulluk; Ev hizmetleri; Ev işçisi kadınlar; Toplumsal cinsiyet; Çok boyutlu yoksulluk; Gender; Multi-dimensional poverty